Hospitalization for the elderly for sensitive causes of primary care (Research, Society and Development, 2022)
Objective: To verify the ambulatory care sensitive conditions prevalence among older adults in the years 2008 and 2018 and associated variables. Methods: Cross-sectional quantitative observational study with data from the national health information system carried out in the city of Passo Fundo-RS in the years 2008 and 2018, with a sample composed of 9,064 authorizations for hospital admissions. The variables age, sex, race/color, address and procedure code were evaluated. The outcome of hospitalizations for sensitive causes was defined based on ICD-10 of the authorized procedure according to the Brazilian Sensitive Conditions to Primary Care List. Descriptive analyzes were performed and for the associations the chi-square test and Fisher's exact tests were applied. Results: Ambulatory care sensitive conditions of the elderly were significant, higher in 2008 when compared to 2018, 33.6% and 27.9%, respectively (p